Assessing the quality of translated modules in an ODL institution: the OUM experience - Nooni Ezdiani Yasin; Nazrai Ahmad Zabidi; Normahliza Aman; P. Rajesh Kumar; Woo Tai Kwan (2019)
Open University Malaysia (OUM) is one of the pioneers of open and distance learning (ODL) in Malaysia. English is the main medium of instruction at OUM. However, the Malay language is the national language of the country and it is estimated that 55% of OUM adult learners are from the Malay speaking background, thus there is a necessity to produce bilingual modules to meet their needs and improve their access to education. The university has produced 82 bilingual modules as of May 2018. At OUM, the Centre for Instructional Design and Technology (CiDT) is responsible for developing learning materials in OUM, including Portable Document Format (PDF) modules and video lectures. A total of 2,431 modules and 288 video lectures, as of September 2018, have been produced. The overall purpose of this paper is to determine whether a relationship exists between the quality of translated modules and the translators’ qualifications. This research finding is also concerned with creating a pool of competent translators to further enhance the quality of translated modules. The basic design of data for this research paper was gathered from a translation project for OUM’s Cluster of Business and Management conducted in six phases from July 2013 to May 2015. This research will review selected modules against the translators’ background and the quality ratings given by OUM academics. A total of 53 translated modules from English to Malay will be reviewed. It is hoped that the findings will help OUM gain new insights into ways of coming up with quality translated modules to meet the needs of learners. (Abstract by authors)